2022
DOI: 10.1177/15280837221095203
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-performance filter from Agave americana fibre/polyacrylonitrile nanofibre membrane for Cd, Pb (II) and organic contaminants removal from aqueous solution

Abstract: Constructing an easily recyclable and reusable filter is highly efficient for removing Cd, Pb2+ and organic contaminants from aqueous solution. This study investigates the optimization of Cd, Pb2+ adsorption process by thiol functionalized Agave americana fibre. Additionally, polyacrylonitrile (PAN) nanofibre membrane is used as a substrate to filter the organic contaminants. The properties of adsorbents are characterized by various techniques such as Attenuated Total Reflection- Fourier transforms infrared sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…AAFs, either in their raw state or after blending/surface modification, have been used in a wide range of applications. These applications include the adsorption of heavy metals such as Cd (II) and Pb(II) [25,26], phytoremediation of soil contaminated with cadmium [27], reinforcing the TiO2/polyester resin-based composites [28] and adsorption of dyes i.e., MB [29], malachite green [30], sumfixe supra red [31], alpacelle lumiere brown [31] and alpacide yellow [32]. Gupta et al [33] grafted Luffa cylindrical fibre and ficus carica fibre [34], Sharma et al [35] grafted Hibiscus cannabinus fibre, Pomicipic et al [36] grafted pineapple leaf fibre and Hakram et al [37] grafted bacterial cellulose with acrylic acid (AAc) for adsorption of MB dye from wastewater and reported that AAc graft copolymerization significantly impacts the adsorbing nature of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…AAFs, either in their raw state or after blending/surface modification, have been used in a wide range of applications. These applications include the adsorption of heavy metals such as Cd (II) and Pb(II) [25,26], phytoremediation of soil contaminated with cadmium [27], reinforcing the TiO2/polyester resin-based composites [28] and adsorption of dyes i.e., MB [29], malachite green [30], sumfixe supra red [31], alpacelle lumiere brown [31] and alpacide yellow [32]. Gupta et al [33] grafted Luffa cylindrical fibre and ficus carica fibre [34], Sharma et al [35] grafted Hibiscus cannabinus fibre, Pomicipic et al [36] grafted pineapple leaf fibre and Hakram et al [37] grafted bacterial cellulose with acrylic acid (AAc) for adsorption of MB dye from wastewater and reported that AAc graft copolymerization significantly impacts the adsorbing nature of biomass.…”
Section: Introductionmentioning
confidence: 99%